Histamine in Tuna Sandwiches and Hygienic Status of Some School Food Vendor Premises in Tripoli city, Libya. - Hassan, Tawfik; Abuhlega, Thuraya; Lawila, Aml; Alkekli, Salah (Journal of medical and pharmaceutical sciences, 2017)
Tuna sandwiches are prepared either in school’s premises or at home and sold to pupils/students during break at schools in Tripoli city- Libya. These sandwiches are nutritious meal for pupils/students however, they are also recognized a major public health risk if they are not prepared and served under good hygienic and sanitary conditions. The present study was conducted to investigate levels of histamine in random samples of tuna sandwiches collected from school food vendor premises and asses the hygienic and sanitary status of these premises as well as the sandwich handlers. Histamine in tuna sandwiches ranged 0.052 – 0.485 mg%. the results were below the maximum allowed level established in Libyan standard 10 mg% and Food and Drug Administration 5 mg%. Despite the low histamine contents obtained in the tuna sandwiches samples. However, Inspection results of the school’s food vendor premises and sandwich handlers showed weak points that need to be rectified which are: sandwiches must be kept in a proper clean container and held under refrigeration until time of serving to pupils/students. The sandwich handlers must have a valid health certificate before allowed to work in such premises and wear gloves, hair cover and appropriate custom for work.